Towards a New Comprehensive Partnership - Economic and Trade Relations between the Gulf Cooperation Council and the European Union - Kalicka-Mikołajczyk, Adriana (University of Wroclaw. Faculty of Law, Administration & Economics, 2015)
The Gulf Cooperation Council is a regional organisation, with six members: Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and the United Arab Emirates. Set up in May 1981, its objectives are to enhance coordination, integration and inter-connection among its member States. Relations between the European Union and the Gulf Cooperation Council are governed by a Cooperation Agreement signed on 15 June 1988 as well as a Joint Action Programme agreed on 14th June 2010. The main objective of the Cooperation Agreement is to contribute towards strengthening stability in a region of strategic importance and to facilitate political, trade and economic relations. The GCC States possess huge oil reserves, which are crucial for the EU and all six GCC Members are developing countries that are in need of the technology, experiences, and various products of the EU. Therefore, Article 11 of the Cooperation Agreement provides that the objective is to encourage, develop and diversify trade between the Parties to the highest possible level, and that the two Parties will initiate negotiations leading to an agreement on expanding trade according to the provisions of the Joint Declaration attached to this Agreement. According to which, the main objective of the new trade agreement is to expand trade through taking appropriate measures for improving access for the products of either party to the other party’s markets and liberalizing bilateral trade. Both Parties are committed to negotiations towards a Free Trade Agreement which were initiated in 1990, however in 2008, due to the absence of any progress, the GCC suspended them, but approved the European demand to continue consultations between the two parties, until a common ground for resuming negotiations is achieved. However, informal dialogues are still ongoing and covers: market access for goods, services and public procurement; common rules and disciplines for intellectual property rights; competition; dispute settlement; rules of origin; human rights; illegal immigration and terrorism. The general objectives of this paper are: 1) to analyse the economic and trade relations between the European Community/European Union and the Gulf Cooperation Council since 1981 and 2) to analyse the prospects for the possibility to renovate, to foster and deepen economic and trade relations between these two international organisations in the nearest future in the form of the Free Trade Area.
Keywords: Rada Współpracy Państw Zatoki Perskiej; współpraca międzynarodowa; Unia Europejska